Pulmonary function in an international sample of HIV‐positive, treatment‐naïve adults with CD4 counts > 500 cells/μL: a substudy of the INSIGHT Strategic Timing of AntiRetroviral Treatment (START) trial. (April 2015) - Kunisaki, KM; Niewoehner, DE; Collins, G; Nixon, DE; Tedaldi, E; Akolo, C; Kityo, C; Klinker, H; La Rosa, A; Connett, JE; ,
Abstract : Objectives: The aim of the study was to describe the prevalence and correlates of chronic obstructive pulmonary disease (COPD) in a multicentre international cohort of persons living with HIV (PLWH). Methods: We performed a cross‐sectional analysis of adult PLWH, naïve to HIV treatment, with baseline CD4 cell count > 500 cells/μL enrolled in the Pulmonary Substudy of the Strategic Timing of AntiRetroviral Treatment (START) trial. We collected standardized, quality‐controlled spirometry. COPD was defined as forced expiratory volume in 1 s:forced vital capacity (FEV1 :FVC) ratio less than the lower limit of normal. Results: Among 1026 participants from 80 sites and 20 countries, the median age was 36 [interquartile range (IQR) 30, 44] years, 29% were female, and the median time since HIV diagnosis was 1.2 (IQR 0.4, 3.5) years. Baseline median CD4 cell count was 648 (IQR 583, 767) cells/μL, median viral load was 4.2 (IQR 3.5, 4.7) log10 HIV‐1 RNA copies/mL, and 10% had a viral load ≤ 400 copies/mL despite lack of HIV treatment. Current/former/never smokers comprised 28%/11%/61% of the cohort, respectively. COPD was present in 6.8% of participants, and varied by age, smoking status and region. Forty‐eight per cent of those with COPD reported lifelong nonsmoking. In multivariable regression, age and pack‐years of smoking had the strongest associations with FEV1 :FVC ratio ( P  < 0.0001). There was a significant effect of region on FEV1 :FVC ratio ( P  = 0.010). Conclusions: Our data suggest that, among PLWH who were naïve to HIV treatment and had CD4 cell counts > 500 cells/μL, smoking and age were important factors related to COPD. Smoking cessation should remain a high global priority for clinical care and research in PLWH.